Learning in community: towards a culturally-responsive education. A case study in the Huasteca region (REM. Chilean Journal of Musical Education, 2025)
In this paper, we discuss the initial findings of a 7-day community-immersive learning experience in which a cohort of music education students of the University of Veracruz had the opportunity to learn the way in which local Huastecomusic culture bearers are transmitting their musics traditions to children and youth. We provide findings from a focusgroup that took place during the last day of the communityimmersive learning experience. In this focus group, the musiceducation students, a community-led organization member representative, a research assistant, a music professor/researcher,and a researcher.
Keywords: Culturally-responsive music education; Communityimmersive learning experience; Huasteca region